Digital Image Watermarking Using LSB Method - ., Maulidin (2011)
Nowadays, the transmision of data is very important and it has been carried out by using digital media (Internet, e-mail). There are some problems that may occur in the transmission of digital media data which is associated with data security level to be sent. Base on that condition, the thought of doing data concealment are emerge. Digital image is one of the most common media used by the community. Digital watermarking is one of cryptography methods which used to hide data into digital image so that the data sent cannot be identified by the irresponsible people. Data encryption is used to improve the security of data to be sent. Internet as the world's largest network system that connects nearly all computer worlds, making all the c omputers in the world is increasingly easy to exchange data. There are so many digital data falsification has occurred. Digital falsification of data aimed to succeed the counterfeiting syndicate these hidden plans. the falsification problem of digital data will from be resolved by applying the watermarking using LSB method (Least Significant Bit).